Sensemaking Workshop Preparation Guide and Facilitator Guide and Sensemaking Training - and UNDP (UNDP, 2022)
Based on experience from running Sensemaking workshops for UNDP offices and government partners, the Asia-Pacific Regional Innovation Centre developed the Sensemaking Preparation Guide and Facilitator Guide to share its knowledge with teams and organization that are interested in using the Sensemaking process.